Telemedicine and the standard of care: a call for a new approach? - Holčapek, Tomáš; Šolc, Martin; Šustek, Petr (Frontiers in Public Health, 2023)
Telemedicine, understood as the provision of health care by a health professional to a patient who is physically not in the same location as the health professional, has many actual and potential benefits. It also has some disadvantages though, including a higher risk of misdiagnosis or another unfavorable outcome of certain remotely-provided services. In principle, the regime of legal liability for medical malpractice is the same for telemedicine as for traditional physical care. The general outline of the standard of care, which includes respect for medical science, the patient's individuality and objective possibilities, is abstract and flexible enough to be used for remote care without the need for redefinition. The quality of health care should be evaluated on the basis of the whole scale of risks and benefits it brings to a particular patient, including accessibility and comfort. In general, it should be permissible to provide a medical service remotely on the condition that its overall quality is at least as good as its comparable physical alternative. In other words, certain decrease in quality of some aspects of remote care can be compensated by other advantages. In terms of public health, support for telemedicine may bring a great improvement in the access to health care, and thus help significantly the individual members of the population. From the individual perspective, respect for personal autonomy implies that a patient should have every right to opt for a remote service, provided that there exists a true choice between meaningful options which is made on the basis of full information. If telemedicine is to fulfill its potential without sacrificing the protection of patients and their rights, reasonable guidelines for remote services need to be defined for particular medical fields, and for specific procedures within them. Among other issues, these guidelines must address the question of when it is necessary to refer the patient to physical care.